Play-based learning: A pedagogical approach for social skills development in ECE learners in Zambia - Grant Mapoma Mwinsa; Murunwa Dagada (Social Sciences and Humanities Open)
The link between pedagogical approaches and skills development in Early Childhood Education (ECE) has been a topic of interest in the recent past. Research has shown that early childhood Indigenous education fosters child development as children learn from adults who are experienced in a local game. The study was based on indigenous knowledge systems (IKS), Piaget's theory of play and Vygotsky's sociocultural theory as theoretical underpinnings. This study aimed to examine the effectiveness of play-based learning as a pedagogical approach for enhancing skills development in ECE learners in Zambia. The study involved ten ECE teachers from four purposively selected primary schools in the Chibombo District of Zambia. The study was qualitative and used a participatory action research (PAR) design through an interpretivist paradigm. Interviews and lesson observations were conducted to ascertain the use of a play-based learning approach in lessons taught by ECE teachers. The study found that traditional games, when used in play-based learning, enhance the acquisition of social skills such as resilience, self-esteem, self-confidence, cooperation, and children's agency. Traditional games through play-based learning were significant in teaching and learning of pre-primary school learners as they led to holistic child development. The study concludes that play-based learning using traditional games can support the development of social skills such as cooperation, teamwork, resilience, self-esteem, self-confidence, appreciation of culture, respect for elders and acquisition of values, and morals and customs in learners. Studies on play-based learning approaches that support the acquisition of social skills in preschool children in Zambia are very limited. This study addresses this gap. The article recommends that Indigenous games be included in the Early Childhood Education curriculum and encourage play-based learning through policy financing for culturally appropriate education, teacher preparation, and community involvement.